R-loops: a key driver of inflammatory responses in cancer - Seo Yun Lee; Min Jae Kwak; Jae Jin Kim (Experimental and Molecular Medicine)
Abstract R-loops, which are noncanonical three-stranded nucleic acid structures formed when RNA hybridizes with complementary DNA strand while displacing the other DNA strand, have emerged as crucial players in cellular homeostasis and cancer pathogenesis. Here we explore the intricate relationship between R-loops and inflammation in the context of cancer development and progression. R-loops can trigger inflammatory responses through various mechanisms, including DNA damage induction, genome instability and activation of innate immune pathways, particularly in cancer cells, where R-loop regulation is frequently dysregulated. In the tumor microenvironment, R-loop-mediated genomic instability contributes to inflammatory signaling cascades, affecting both cancer cells and the surrounding tumor microenvironment. We discuss how aberrant R-loop formation influences key inflammatory pathways, including the cGAS–STING axis and NF-κB signaling, and their subsequent effects on tumor progression. Furthermore, we explored how cancer cells manipulate R-loops to modify their inflammatory microenvironment, potentially affecting their therapeutic responses. Understanding the complex interplay between R-loops and cancer-associated inflammation provides novel insights into tumor biology and opens new avenues for therapeutic intervention. This Review summarizes the current knowledge on R-loop biology in cancer, its inflammatory consequences and potential strategies for targeting R-loop-mediated inflammation in cancer treatment, underscoring the importance of this emerging field in cancer medicine.